UTILIZATION OF COASTAL AREAS AND SMALL ISLANDS - Ansory, Ahmad; Hasibuan, Melkisedek; Yudistira, Yudistira; Manalu, Omena (Communale Journal, 2023)
Indonesia, as an archipelagic country with tens of thousands of islands and thousands of peer areas, should be our country can take advantage of the great gift of this condition. Our constitution shows that we must use natural resources for the most excellent welfare of society. However, at this time, it is inversely proportional to what we expect; regulation after regulation, we strive in the Management of these natural conditions, which, until now, the state of our country is just like that. So, the purpose of this writing is to discuss the view of the law as a legal norm in the Implementation of the management of coastal areas and small islands and what opportunities can be utilized by communities around coastal areas and small islands in their economic development and the sustainability of nature itself. The methodology we use is a normative juridical method; we want to discuss from a legal point of view how the rules apply and from some reliable literature that discusses the management and utilization of coastal areas and small islands.